Polimorfismo isoenzimático en cuatro razas y un híbrido de Bactris gasipaes (Palmae) - Rojas-Vargas, Sonia (1999)
he study of genetic diversity in peach palm (Bactris gasipaes K.) is impDrtant fDr the breeding wDrk Dn Ihis Palm and tD cDrrDbDrate the hYPDtheses Dn its Driglns. FDr that purpDse it is necessary tD use alteroative techniques tD cDmplement the mDrphDlDgical studies traditiDnally made. One Df the techniques thar responds tD that need is iSDzyme electrDphDresis. The iSDzymes are biDchemical markers Df impDrtance in the stud)/ Df genetic variability in plants Df econDmic impDrt¡¡nce, because they are the primary products Df genetic expressiDn. This wDrk is an electrDphDretic analysis Dn gels of pDlyacrilamide tD study phenetic relatiDns using twelve iSDzymes Dn fDur races and an spDntaneDus hybrid Df peach palmo The biDlDgical material used carne frDm the germplasm bank from LDS Diamantes Experimental Statión, Guápiles-CDsta Rica.FDur races and a hybrid were selected frDm that cDllectiDn. They represented different prDcedences with mDrphDlDgical differences as weł as having particular geDgraphical distriblitiDn patteros; they were: Tembé-Chapare (BDlivia-BD), Pará -Belem (Brasil-Bra), Utilis Guápiles (CDsta Rica-CR), Tuira-Darién (Panamá-Pa) and Yurimaguas (Perú-Pe). Five trees Df each race and the Yurimaguas hybrid were studied. Different tissues were tried: leaf, adventitiDus roots, spines, masculine flDwers and ripe fruits. An standard native and discDntinued method was established Dn a pDlyacrilamide matrix fDr the analysis Df twelve iSDzymes: (PRX, EST, ACp, DIA, G6PDH, ME, MDH, GOT, ADH, PGI, PGM and SOD). The amDunt Df tissue used was 1. 5 g, with 20 min C\arificatiDn time at 15000 gravity value and a temperature Df 400C. The protDCDl propDsed by Baaziz & Saaidi (1988) was fDllDwed with a mDdificatiDn Df CDncentratiDn Df the phDsphate buffer sDlutiDn frDm 0,005 M tD O. 1M with a 50 tD 200 vDlts gradient . . The roDt, flDwer and spine tissue were difficult tD hDmDgenize because Df their high fiber content. The fmit has tDo. much Dil and starch, which distort the banding. FDr thDse reasDns they were discarted. The leaves were selected because tbey are easy tD hDmDgenize and are available all year round. The standardized electrDphDretic methDd allDwed the effective use Df ten Df the twelve iSDzymes in the leaf tissue. ThDse ten iSDzymes shDwed phenetic pDlymorphism and are cDnsidered useful pDlymDrphic markers fDr genetic and phenetic diversity studies in Bactris gasipaes. A discriminant marker fDr the Utilis-Guápiles race was fDund with the PRX iSDzyme, which ShDWS an additiDnal lDcus Dnly in material frDm that procedence. The cDnglDmerate statistical analysis shDwed that the races and hybrid studies can be placed in three grDUpS: Dne is fDrmed by Pará and Tembé, the secDnd Dne by Utilis and Tuira, and the hybrid Yurimaguas is a class by itself and althDUgh it seems a bit c\Dser tD Utilis-Tuira, it is suspected that has its Drigin from \InknDwn parents. These results fit previDus mDrphDlDgical interpretatiDns. A genetic analysis was nDt made because Df the small sample size, but methDdDIDgical procedures were established fDr future research projects using larger pDpulatiDns tD study peach palm iSDzyme electrDphDretic diversity